Analysis of the Quality of Human Development in ASEAN-5 Countries - Erlitasari, Regita Nanda; Suliswanto, Muhammad Sri Wahyudi (International Journal Labs, 2024)
The development of science and knowledge that is increasingly modern is one of the things that is quite beneficial in all aspects of life. With technological advancements, every country is competing to improve development in an effort to realize the welfare of its population. The use of data in this study is secondary data sourced from the World Bank and the United Nations Development Programme (UNDP). The results of this research found that variables, government spending in the education sector had a significant impact while GDP and government expenditure in the health sector did not have a significant impact on the HDI of five ASEAN countries, namely Indonesia, Malaysia, Thailand, the Philippines and Vietnam. The impact of GDP, government spending on education, and government spending on health on the quality of human development in five ASEAN countries are the targets of this study.